Implementation of the Community Nursing Model in Improving Postoperative Care Compliance for Postoperative Patients at Home - Anita Lontaan; Darmi Arda; Wahyudi Hardi (Edukasi Ilmiah Indonesia, 2026)
Introduction: Postoperative care at home remains a critical challenge, particularly in community settings where patients often lack adequate knowledge and support, leading to low compliance and increased risk of complications. Community-based nursing approaches offer a strategic solution to improve patient outcomes through education and continuous monitoring. This community service program aimed to improve postoperative care compliance among patients at home by implementing the Community Nursing Model. Methods: A quasi-experimental one-group pretest–posttest design was employed involving 35 postoperative patients. The intervention included health education, wound-care demonstrations, medication management counselling, and home visits with family involvement. Data were collected using questionnaires and observation checklists, and analyzed using comparative statistical methods. Results: The findings showed a significant improvement in all measured indicators. Mean knowledge scores increased from 58.2 to 84.3, compliance scores improved from 62.4 to 81.6, and proper wound care practices rose from 54% to 88%. These results indicate enhanced patient understanding, skills, and adherence following the intervention. Conclusion: The Community Nursing Model is effective in improving postoperative care compliance in community settings. Integrating education, family support, and continuous monitoring can strengthen home-based care and reduce the risk of complications.